Review to Daniel Hutto and Erik Myin’s Evolving Enactivism: Basic Minds Meet Content. MIT Press, 2017. - Silva, Marcos; Brito, Carlos; Ferreira, Francicleber (Princípios: Revista de Filosofia (UFRN), 2019)
In this review, Hutto and Myin’s new book “Evolving Enactivism: Basic Minds Meet Content” (2017) is critically presented. Although they do not provide a detailed cognitive science theory based on their Radical Enactive approach, one may say that Hutto and Myin originally address the perennial philosophical issue about our nature as human beings giving an impossible-to-neglect enactivist contribution to the current state-of-art in the discussion concerning embodied cognition.